Minat Belajar Siswa Terbaik Menggunakan Aplikasi E-Learning Edmodo Dengan Metode Weighted Product SMK Cerdas Murni - Ermayanti Astuti; Putri Yunita (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Determining student interest in learning, of course, the material studied has a lot to do with exact sciences, especially in the field of science. Various constraints and factors that cause learning in the field of science to be not optimal require the need for changes to learning in the field of science that can be used as an alternative in improving learning science majors. E-learning is an alternative in science learning, considering that unlimited access to information via the internet should be utilized by students properly, especially so that students can get meaning from subjects in the science field. The analysis carried out in the research is the decomposition of a complete information system into its component parts in order to identify and evaluate the problems, opportunities, obstacles that occur and the expected needs so that improvements can be proposed and determine the best student learning interests. The method used in the implementation of this research activity will be carried out with a sampling process equipped with training on the use of Edmodo-based e-learning applications to make decisions on the best student interest in the learning system. The results of these decisions can be obtained by using the Weighted Product method. Learning media that is based on Edmodo can be used as an alternative in classroom learning, makes it easy for teachers to provide subject matter by interacting with students online and offline and can monitor studentactivity in study groups and can carry out evaluations.